The trouble with Violet - Mazer, Anne. (New York : Scholastic/Little Apple, 2007)
When strange things start happening and eight-year-old Mabel, who is very sensible, cannot figure them out, she discovers a family secret that affects her younger sister Violet.
Keywords: Magic -- Fiction; Sisters -- Fiction